2016
DOI: 10.1159/000447828
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Subsequent Risk of Acute Childhood Leukemia: a Meta-Analysis of Observational Studies

Abstract: Background: Preterm birth (PTB) has been recognized as a crucial long term risk factor for multiple non-communicable diseases. However, studies between the relationship of PTB and the risk of acute childhood leukemia have yielded inconclusive results. Therefore, we performed a meta-analysis to systematically review the current literature to investigate whether PTB is associated with increased risk of acute childhood leukemia. Methods: Three electronic databases (PubMed, Web of Science, and EMBASE) were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
1
11
1
Order By: Relevance
“…Subgroup analyses by study types further showed postterm birth increased the risk of childhood leukemia and ALL in cohort studies. A previous manuscript published by Huang et al [9] found that preterm delivery was associated with increased risk of acute childhood leukemia and AML; there was no significant relationship between preterm birth and ALL. The same trend with different results were reported in our article, mainly because we brought into different studies that relied on a diverse search strategy and inclusion criteria.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Subgroup analyses by study types further showed postterm birth increased the risk of childhood leukemia and ALL in cohort studies. A previous manuscript published by Huang et al [9] found that preterm delivery was associated with increased risk of acute childhood leukemia and AML; there was no significant relationship between preterm birth and ALL. The same trend with different results were reported in our article, mainly because we brought into different studies that relied on a diverse search strategy and inclusion criteria.…”
Section: Discussionmentioning
confidence: 93%
“…The same trend with different results were reported in our article, mainly because we brought into different studies that relied on a diverse search strategy and inclusion criteria. In addition, the analysis reported by Huang et al [9] did not examine postterm delivery. We added six new studies [11,13,14,17,19,23] and investigated the relationships among postterm delivery and childhood leukemia, ALL and AML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis evaluating the impact of preterm birth on childhood leukemias also noted no increase in the risk of ALL or all leukemias combined, but found a modest increase in the risk of AML[38]. However, the studies included for summary effects were older and numerous samples were entirely duplicated.…”
Section: Discussionmentioning
confidence: 99%